Synthetic studies directed towards the antineoplastic macrolide bryostatins. - Rey, Allan W. (University of Ottawa (Canada), 1990)
This thesis describes stereocontrolled and practical routes to the C(1)-C(9), C(17)-C(20), and C(21)-C(27) synthons of bryostatins, which are a closely related family of 20-membered ring lactones embedding 1,3-polyol units. Bryostatins are isolated in minute quantities from the marine Bryozoan Bugula neritina and possess exceptional antineoplastic activity. Membrane-enclosed enantioselective enzymatic hydrolysis was successfully employed for the generation of gram quantities of the versatile building block (3R)-methoxymethoxypentadioic acid, monomethyl ester (51) (Chapter 2). This compound was used in the synthesis of the C(1)-C(5) segment of bryostatins. Preliminary synthetic studies towards the C(1)-C(9) subunit are described in Chapter 3. Wittig and dithiane approaches were unfortunately unsuccessful for the connection of an enzymatically derived 5 carbon unit with a D-pantolactone derived 4 carbon unit. Chapter 4 describes the practical synthesis of the C(1)-C(9) fragment of bryostatin in forms suitable for both structure/activity studies and synthetic elaboration. The pivotal step utilized a diastereoselective Mukaiyama aldol condensation of a diketene derived silylenol ether with an enzymatically derived chiral $\beta$-alkoxyaldehyde. Chapter 5 details the conversion of D-pantolactone and of D-galactono-1,4-lactone into the C(17)-C(20) and C(21)-C(27) synthons of bryostatins via a chiron approach. A study of nucleophilic additions onto chiral substituted $\gamma$-lactol templates is discussed in Chapter 6. This provided valuable information regarding the coupling of the C(17)-C(20) and C(21)-C(27) segments of bryostatins. As well, the results demonstrate the potential utility of $\gamma$-lactols as templates--a relatively unexplored area in asymmetric synthetic chemistry.
Keywords: Chemistry, Biochemistry.